IMPLEMENTASI LARASITA (LAYANAN RAKYAT SERTIPIKAT TANAH) SEBAGAI UPAYA PENINGKATAN KUALITAS PELAYANAN PUBLIK - DEWI SIMBOLON , Endang Sri Santi, Suhartoyo*) (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Registration of land is an important issue in the BAL and as a means for the government to collect data over a land rights for all land in the territory of the Republic of Indonesia and not be a clear ownership wastelands also avoid chaos in the control of land rights, land registration is due early of the birth of a proof of ownership of land. Basic Agrarian Law and the mandate of Article33 paragraph (3) of the 1945 Constitution embodied the built and developed LARASITA that depart from the will and motivation to get closer with the National Land Agency, as well as changing the paradigm of the principal duties and functions of the BPN wait or passive to active or proactive (Introduction Regulation of Head of National Land Agency of the Republic of Indonesia No.. 18Year 2009 About LARASITA BPN_RI). The problems are formulated, namely the implementation of How People Services Land Certificate (LARASITA) by Jatipurwo Village Land Office, District Rowosari, Kendal and was with the People's Service Certificate Program Land (LARASITA) can improve the quality of public services for rural Jatipurwo, District Rowosari, KendalApproach method is empirical juridical approach, the specification using descriptiveanalytical research, while the population of all parties associated with the implementation LARASITA program and sampling methods are purposive sampling is done by taking the subject and the object based on the specified destination. The data collection methods the authors use the technique of interviewing her (interview) and based on existing data (primary and secondary) that have been collected to allow for qualitative data analysis.Based on the results of the study showed that the implementation of the land through Program LARASITA certificated Village Jatipurwo managed and implementation services provided by the District Land Office Kendal in accordance with the Service Standards and Regulation in the Land Act No. 25 of 2009. This can be evidenced by the level of public satisfaction with the services provided so that the number of applicants who want certificated the land with increased LARASITA Program.Implementation LARASITA in District Rowosari Village Jatipurwo generally went well, successful and have high levels of citizen satisfaction are quite satisfied with the service provided both the BPN-RI Land Kendal and the village in charge of running the Program Larasita Jatipurwo village which has a number of applicants to follow the growing Larasita Program. To further provide more baih longer required continuous extension and additional car LARASITA.